THE PHYSICAL EDUCATION CLASSES WITH THE LOOK OF BODY CULTURE IN STUDENT PERSPECTIVE 8 TH AND 9 TH YEAR (Fiep Bulletin - online, 2015)
This study examined the student's view of physical education class and the aspect of Physical Education called Body Culture. Were chosen for the research students of the Municipal Public Education Network of the Eighth and Ninth year of elementary school, who answered a questionnaire about the contents of Physical Education classes and the Body Culture. The study aimed to investigate the general idea that the student has about the class Physical Education and the Body Culture. The results have shown that students have some knowledge of Body Culture, found that physical education as a discipline is highly regarded, not being seen as a sports practice, but as a way to acquire healthy habits. Therefore, so it is necessary an elaboration of new studies on the subject, so that they can further questions about the point of view of students.
Keywords: Physical Education; Body Culture; Schooling.